Do agricultural imports and exports cointegrate? Evidence from 13 OECD countries: - Manuchehr Irandoust (Italian Review of Agricultural Economics (REA), 2022)
Previous studies have investigated the behaviour of trade flows at the aggregate level, thus they suffer from aggregation bias. In this paper, we use the sectoral data on agricultural exports and imports to examine whether they cointegrate. The likelihood-based panel cointegration technique is applied to investigate the long-run convergence between the variables for 13 industrialized countries. The results indicate that a long-run steady-state relationship exists between the variables for most countries in the sample. The policy implications of our findings are that agricultural trade does not lead to the violation of international budget constraints and, more importantly, there is no productivity gap in the agriculture sector between the domestic economy and the rest of the world, implying a lack of permanent technological shocks to the domestic economy. The results also provide support for intra-industry trade in the agriculture sector.
Keywords: E60; F31; F14; 330; agriculture; imports; exports; cointegration